Late Middle Palaeolithic occupations in Ciemna Cave, southern Poland. (3rd March 2016) - Valde-Nowak, Paweł; Alex, Bridget; Ginter, Bolesław; Krajcarz, Maciej T.; Madeyska, Teresa; Miękina, Barbara; Sobczyk, Krzysztof; Stefański, Damian; Wojtal, Piotr; Zając, Mirosław; Zarzecka-Szubińska, Katarzyna
Abstract : Recent excavations in Ciemna Cave in the Prądnik valley near Ojców, southern Poland have brought to light new stratigraphic and techno-typological evidence concerning Late Middle Palaeolithic groups and their cultural affinities. In 2007, excavations began in the hitherto-unexplored main chamber of Ciemna Cave, with the goal of clarifying the results of previous work in other parts of the cave. During excavation the rocky floor of the cave was reached. About 1000 stone artifacts have been collected to date. Three cultural traditions have been documented: Mousterian, Taubachian, and Micoquian. Within the Micoquian tradition, three cultural levels were observed, which enriches the previous understanding of occupational phases at the site. These findings permit revision of the traditional terms "Prądnik industry" and "Prądnik technique."